EFFICIENCY OF THE AMINOACID-BASED MIXTURES IN BRINGING RELIEF FOR THE SYMPTOMS OF THE COW'S MILK PROTEIN ALLERGY: SYSTEMATIC REVIEW - S.H. Murch; L.S. Namazova; T.E. Borovik (Union of pediatricians of Russia, 2008)
In the given systematic review, the authors evaluated the efficiency of the amino acid based mixtures among the patients, suffering from the cow's milk protein allergy. They have studied the electronic and bibliographic databases. The researchers accounted for the patients of any age, suffering from the cow's milk protein allergy or similar symptoms. The task was to compare the aminoacid based mixtures with highly hydrolyzed mixtures, soy mixtures and cow's milk/cow's milk based mixtures. They showed that the use of the amino acid based mixtures is safe and efficient among the infants with the confirmed or suspected cow's milk protein allergy. The data of the randomized controlled studies, comparing amino acid based mixtures with highly hydrolyzed mixtures, witnesses that both types of mixtures are equally efficient in reducing the symptoms of the cow's milk protein allergy in the confirmed or alleged allergy cases. This review demonstrates the clinical impact of the amino acid based mixtures both upon certain symptoms and growth of the infants and children with the cow's milk protein allergy, who have zero tolerance towards the highly hydrolyzed mixtures.Key words: aminoacid-based mixtures, cow's milk protein allergy, highly hydrolyzed mixtures, soy mixtures, systematic review.